The Perspective of Civil Law in Legal Protection for Children in Bullying Cases - Hotmaida Simanjuntak; Monalisa Siahaan; Kondios Meidarlin Pasaribu (Faculty of Law, Universitas Pekalongan, 2025)
Abstract Civil law plays a crucial role in protecting children who are victims of bullying by providing a legal basis to claim compensation for material and immaterial damages. Article 1365 of the Civil Code, which regulates unlawful acts, allows bullying victims to seek compensation from the perpetrator or negligent parties, such as schools. Additionally, the civil law approach supports dispute resolution through mediation, in line with the best interests of the child principle. Preventive protection can also be implemented through anti-bullying policies in schools that require educational institutions to be responsible for student safety. However, the implementation of civil law in bullying cases faces challenges, such as difficulties in proving psychological harm and a lack of public understanding of legal rights. Therefore, broader legal awareness and legal education are needed to strengthen children's protection against bullying .